A Comparative Study of Phosgene Sensing Using Carbon and Boron Nitride Nano Materials – A DFT Approach - Kweitsu, E.O. (University of Ghana, 2021)
Phosgene (COCl2), a valuable industrial compound, maybe a public safety and health risk due to potential abuse and possible accidental spillage. Conventional techniques suffer from issues related to procedural complexity and sensitivity. Therefore, there is a need for the development of simple and highly sensitive techniques that overcome these challenges. Recent advances in nanomaterials science offer the opportunity for the development of such techniques by exploiting the unique properties of the nanostructures. In this study, we investigated the potential of six types of nanomaterials: three carbon-based ([5,0] CNT, C60, C70) and three boron nitride-based (BNNT, BN60, BN70) for the detection of COCl2. The local density approximation (LDA) approach of the density functional theory (DFT) was used to estimate the adsorption characteristics and conductivities of these materials. The results show that the COCl2 molecule adsorbed spontaneously on the Fullerene or nanocages and endothermically on the pristine zigzag nanotubes. Using the magnitude of the bandgap modulation, the order of suitability of the different nanomaterials was established as follows: PBN60 (0.19%) < PC70 (1.39%) < PC60 (1.77%) < PBNNT (27.64%) < PCNT (65.29%) < PBN70 (134.12%). Since the desired criterion for the design of an electronic device is increased conductivity after adsorption due to the resulting low power consumption, PC60 was found most suitable because of its power consumption as it had the largest decrease of 1.77% of the bandgap.
MPhil. Materials Science and Engineering
Keywords: Phosgene Sensing; Carbon and Boron Nitride Nano Materials; Phosgene (COCl2)